Surface-enhanced Raman scattering and micro-Raman imaging of Langmuir-Blodgett films of rhodium phthalocyanine - Gaffo, L.; Constantino, CJL; Moreira, W. C.; Aroca, R. F.; Oliveira, O. N. (Elsevier B.V., 2004)
Rhodium phthalocyanine (RhPc) was synthesized and ultra thin Langmuir-Blodgett (LB) films of RhPc were successfully fabricated. The LB film characterization was carried out using both UV-vis absorption spectra and Raman scattering. The Raman spectroscopy was carried out using 633 and 780 nm laser lines. LB films were deposited onto Ag nanoparticles to achieve the surface-enhanced pre-resonance Raman scattering (pre-SERRS) and surface-enhanced Raman scattering (SERS) for both laser lines, respectively, which allowed the characterization of the RhPc ultra thin films. The morphology of the LB RhPc neat film is extracted from micro-Raman imaging. (C) 2003 Elsevier B.V. All rights reserved.
Keywords: Raman scattering; Langmuir-Blodgett films; rhodium phthalocyanine